Performance evaluations of multi-layers ring network architecture - Chien, Su Fong; Tan, C. P.; You, Ah Heng; Low, Andy L. Y.; Takahashi, K. (The Institute of Electronics, Information and Communication Engineers, 2005)
Performance evaluations of the multi-layers ring network architecture with unicast/multicast function have been done recently by using non-parametric approach. It was claimed that the proposed architecture outperforms the conventional point-to-point multi-layers architecture in terms of the link cost and interface cost. This paper further investigates the impact of the traffic to the nodes in such architecture with unicast capability through optical packet switching simulations. It is found that there are serious packet losses at layer 3 if switches capacity are same at all levels; the required number of wavelengths/optical buffers increases exponentially in order to maintain a given packet loss rate when more layers exist in the architecture. Therefore, it shows that too many layers architecture may affect the networks performances.